2011
DOI: 10.1007/s00380-011-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stroke work between repaired tetralogy of Fallot and normal right ventricular physiologies

Abstract: Adult patients who underwent tetralogy of Fallot repair surgery (rTOF) confront life-threatening ailments due to right ventricular (RV) myocardial dysfunction. Pulmonary valve replacement (PVR) needs to be performed to restore the deteriorating RV function. Determination of correct timing to perform PVR in an rTOF patient remains subjective, due to the unavailability of quantifiable clinical diagnostic parameters. The objective of this study is to evaluate the possibility of using RV body surface area (BSA)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In the study by Lee et al ., RV PER was significantly lower in adult patients who underwent tetralogy of Fallot repair surgery and had deteriorating RV function. Theoretically, PER happens at the rapid ejection period and is a parameter of RV early systole.…”
Section: Discussionmentioning
confidence: 87%
“…In the study by Lee et al ., RV PER was significantly lower in adult patients who underwent tetralogy of Fallot repair surgery and had deteriorating RV function. Theoretically, PER happens at the rapid ejection period and is a parameter of RV early systole.…”
Section: Discussionmentioning
confidence: 87%
“…The PA regurgitant flow and PA obstruction directly affect the RV performance and efficiency as confirmed in our previous work. 26 It showed that a patient with repaired TOF physiology, including PA regurgitation and PA obstruction, had a significantly higher RV SW I compared with a subject with normal RV physiology. Thus, both RV pressure and volume overloading resulting from mainly PA regurgitation and PA obstruction need to be taken into account for long-term follow-up for patients after repair.…”
Section: Discussionmentioning
confidence: 98%
“…The RV SW was calculated by computing the area enclosed by the pressure-volume (P-V) loop by applying Gauss theorem. 24,26 Therefore, RV SW is given by:…”
Section: Energy Transfer Ratio E Mpamentioning
confidence: 99%
See 1 more Smart Citation
“…The right-hand side of Eq. 5b, 5c, and 5d, i.e., the rate of the pressure-flow and kinetic energy terms at the PAs [9], RPA, LPA and MPA, respectively, can be substituted into Eq. 5a while maintaining flow balance at the PAs ( Q MPA  =  Q RPA  +  Q LPA ).…”
Section: Methodsmentioning
confidence: 99%